Assessing the health risk of living near composting facilities on lung health, fungal and bacterial disease in cystic fibrosis: a UK CF Registry study - Muhammad Saleem Khan; Philippa Douglas; Anna L. Hansell; Nicholas J. Simmonds; Frédéric B. Piel (BMC, 2022)
Abstract Aim To explore the health risk of living near permitted composting sites (PCSs) on disease severity in children and adults with cystic fibrosis (CF) across the UK.  Methods A semi-individual cross-sectional study was used to examine the risk of disease severity in people with CF (pwCF) within and beyond 4 km of PCSs in the UK in 2016. All pwCF registered in the UK CF Registry were eligible for this study. Linear and Poisson regressions, adjusted for age, gender, genotype, BMI, Pseudomonas aeruginosa and deprivation, were used to quantify associations between distance to a PCS and percent predicted forced expiratory volume in one second (ppFEV1), pulmonary exacerbations (#IVdays), and fungal and bacterial infections. Results The mean age of the 9,361 pwCF (3,931 children and 5,430 adults) studied was 20.1 (SD = 14.1) years; 53.3% were male; and 49.2% were homozygous F508del. Over 10% of pwCF (n = 1,015) lived within 4 km of a PCS. We found no statistically significant difference in ppFEV1 and #IVdays/year in children. However, in adults, ppFEV1 was -1.07% lower (95% confidence interval (CI): -2.29%, 0.16%) and #IVdays/year were 1.02 day higher (95%CI: 1.01, 1.04) within 4 km of a PCS. Furthermore, there were statistically significant differences in mean ppFEV1 in CF adults with Aspergillus fumigatus (58.2.% vs 62.0%, p = 0.005) and Candida spp. (56.9% vs 59.9%, p = 0.029) residing within 4 km of a PCS. No associations were identified for allergic bronchopulmonary aspergillosis, P. aeruginosa or Staphylococcus aureus. Conclusions This novel national study provides evidence that adults with CF living near a PCS may experience small reductions in lung function, an increased risk of pulmonary exacerbations, and more frequent fungal infections. If confirmed by studies using refined exposure assessment methods accounting for bioaerosol dispersion, these results could have important implications for the living environment of pwCF.